2002
DOI: 10.1159/000063090
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin and Ibuprofen Effect on IL-1ra Production by Mononuclear Cells of Preterm Newborns and Adults

Abstract: The in vitro effect of indomethacin (IM) and ibuprofen (IB) on the production of the interleukin-1 receptor antagonist (IL-1ra) by cord blood mononuclear cells (CBMC) from preterm newborns was compared to that of peripheral blood mononuclear cells (PBMC) from adults. Mononuclear cells (MC) were incubated with lipopolysaccharide (LPS) in the absence or presence of various concentrations of IM and IB. The level of IL-1ra in the supernatants was tested by ELISA. The results showed a lower ability of MC from prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Inflammatory reaction is an essential component of the body defence mechanism. Bessler et al (2002) have reported that 20 µg/ml of IB added to LPS-stimulated PBMC from healthy adults had no effect on IL-1ra secretion. However, at concentrations of 100 and 200 µg/ml, production of this cytokine was significantly suppressed by 11 % and 54 %, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Inflammatory reaction is an essential component of the body defence mechanism. Bessler et al (2002) have reported that 20 µg/ml of IB added to LPS-stimulated PBMC from healthy adults had no effect on IL-1ra secretion. However, at concentrations of 100 and 200 µg/ml, production of this cytokine was significantly suppressed by 11 % and 54 %, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…However, it has been shown that the capacity of mononuclear cells from preterm newborns to produce IL-1ra and IL-1ß is lower than that of adult cells [22][23][24][25][26][27][28], a phenomenon that could be attributed to the immaturity of the preterms' immune system. It is therefore suggested that the lack of an association between IL-1ra gene polymorphism and the risk of sepsis in preterm neonates may be related to the lower capacity of the neonatal cells to produce IL1ra and IL-1ß, cytokines important in controlling the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Due to low volumes of cord blood available in the present work, PBMCs from adults were used to obtain sufficient amounts of mononuclear cells. Since CBMCs are immature and may therefore respond differently to exposure than PBMCs from adults (Bessler et al, 2002;Bessler et al, 2007;Goldberg et al, 2008), the possibility of different effects of exposure to the 12 investigated substances for the CBMCs and PBMCs cannot be excluded.…”
Section: In Vitro Assaymentioning
confidence: 99%